Endocrine Disruption: Biological Basis for Health Effects in Wildlife and Humans - Norris, David O; Carr, James A (Oxford University Press, 2005)
This book addresses the biological effects of the reasonably large number of classes of compounds that have been recognized as endocrine disrupters. These compounds have been found to persist as pollutants in the environment, and have been blamed for causing developmental disorders and/or fertility problems in fish, amphibians, reptiles, birds, and possibly humans. This book presents the relevant fundamentals of the endocrine systems of animals and humans, the toxicology, developmental toxicology, ecology, and risk assessment methods, and lays out the current state of understanding for the whole field, organized by the classes of compounds that have been identified as endocrine disrupters.